A new approach to increased land reclamation rate in a coal mining subsidence area: A case‐study of Guqiao Coal Mine, China. (8th March 2022) - Li, Gensheng; Hu, Zhenqi; Yuan, Dongzhu; Li, Pengyu; Feng, Zhanjie; He, Yibo; Wang, Wenjuan
Abstract: Underground coal mining inevitably causes land subsidence which floods in a region with high watertables, which will affect sustainable land development. However, the traditional reclamation (TR) method has a low land reclamation rate. Thus, finding a suitable reclamation approach is crucial to alleviate the conflicts between coal exploitation and land protection. In this article, the Guqiao Coal Mine of China, used as a representative case‐study, has been seriously affected by mining‐induced ponding. First, the dynamic distributions of surface subsidence and land damage from 2007 to 2017 were revealed, based on concurrent mining and reclamation (CMR). Second, the land‐water layout of five reclamation schemes (e.g., no reclamation, TR, CMR I, CMR II, and CMR III) were simulated. Then, a dynamic filling elevation model and filling thickness model were constructed. Finally, the earthwork allocation sequence was optimized. Results revealed: 1) reclaimed land area: CMR III > CMR II > CMR I > TR > no reclamation. 2) Digging depths are directly proportional to the earthwork volumes and land area and are inversely proportional to the water areas, but with an increase in digging depths, the reclaimed land area is relatively lower. 3) CMR schemes had reclaimed 426.31–637.82 ha and 259.62–471.13 ha more land than no reclamation and the TR scheme, respectively. Compared with no reclamation and the TR scheme, CMR schemes can increase the proportion of reclaimed land by 33.77–50.52% and 20.57–37.32%, respectively. Research results provide a reference for increasing the mine reclamation rates in areas with high phreatic watertables.